2022
DOI: 10.1155/2022/3452176
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Algorithm-Based Ultrasound Image Information in Diagnosis and Treatment of Pernicious Placenta Previa

Abstract: This study was to explore the value of the deep dictionary learning algorithm in constructing a B ultrasound scoring system and exploring its application in the clinical diagnosis and treatment of pernicious placenta previa (PPP). 60 patients with PPP were divided into a low-risk group (severe, implantable) and high-risk group (adhesive, penetrating) according to their clinical characteristics, B ultrasound imaging characteristics, and postpartum pathological examination results. Under PPP ultrasonic image inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…It can be seen from Table 1 that when the cloud point data continue to improve, the registration time of the deep learning algorithm method and the proposed method is constantly rising, and the time used by the deep learning algorithm method is higher than that of the proposed method, which proves the registration time of the proposed method [20][21][22][23][24][25]. e proposed method is more efficient methods than deep learning algorithms.…”
Section: Simulation and Analysismentioning
confidence: 94%
“…It can be seen from Table 1 that when the cloud point data continue to improve, the registration time of the deep learning algorithm method and the proposed method is constantly rising, and the time used by the deep learning algorithm method is higher than that of the proposed method, which proves the registration time of the proposed method [20][21][22][23][24][25]. e proposed method is more efficient methods than deep learning algorithms.…”
Section: Simulation and Analysismentioning
confidence: 94%
“…Such as multidisciplinary collaborative management, reasonable selection of surgical methods, etc. [ 19 , 20 ] At the same time, Yang et al [ 21 ] pointed out that ultrasound examination can determine the BF status of the cavity BF in the placental parenchyma and the junction of uterine serosa and bladder; the ultrasound scoring system can confirm whether the subject has PA at the thinnest part of the uterine myometrium with the help of conventional ultrasound signs and other information. The combination of the two can realize complementary advantages and disadvantages and effectively improve the value of disease diagnosis and treatment evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the two can realize complementary advantages and disadvantages and effectively improve the value of disease diagnosis and treatment evaluation. Based on this, it is believed that in clinical practice, to avoid missed diagnosis or misdiagnosis to the greatest extent, conventional ultrasound and ultrasound scoring systems can be integrated to carry out inspection and evaluation for patients with early scar uterine PA. [19][20][21]…”
Section: Group Nmentioning
confidence: 99%
“…Further examples of adverse pregnancy events with an often disastrous maternal and fetal outcome are placental abruption and pernicious placenta previa. Yang et al, therefore, investigated the predictive role of a scoring system for the occurrence of pernicious placenta previa [121], while the research group of Asadpour et al reported a method for identifying placental abruption [122].…”
Section: Placenta and Umbilical Cordmentioning
confidence: 99%